Silences and voids in Chekhov’s poetic: nature as part of the scene in The Seagull and images-poem for a short play - Fuentes, Susana (RUS (Sao Paulo), 2022)
In Anton Chekhov’s short stories, space is shaped as the story begins, landscape speaks of presences, memories, voids. And nature itself also appears as a vivid character. Conversation is composed of silences and space. In “Verotchka”, nature takes part in the action, shadows move from one place to another, clouds, trees, mist. The storm at the end of the short story “The murder” speaks of desolation and loneliness, but also of strength and life: out of darkness, nature opens a space, a wild space, to converse with time. And in Chekhov's plays, nature forges this flow of life on the stage, people in their silences, the unspoken, amidst the expectations, the objects, and the sounds on the stage. In The Seagull, the play within the play – the monologue written by Treplev and played by Nina in front of the lake – we encounter a text that has no place, yet still is very close to our times, for it speaks of emptiness where a world of losses can be found. Silences ask to be heard – and this poor moon lights its lantern in vain. Silences that triggered image-poems for a short play.